Kehadiran Aplikasi Digital pada Proses Pelaporan Dana Bos Madrasah Aliyah: Apa Saja Kendala dalam Implementasinya? - Abdillah, Malkan Yahya; Aisyah, Siti (ALSYS, 2022)
The purpose of this study was to find out the obstacles in implementing digital applications in the reporting process of School Operational Assistance Funds at Madrasah Aliyah. The research method used is descriptive research method with a qualitative approach. Data collection methods used in this study were observation, focus group discussions, and interviews with 3 informants. The data from this study were processed using Five Whys Analysis. The results of this study indicate that the obstacles experienced by the staff who are responsible for the reporting process of the School Operational Assistance Fund are caused by the lack of socialization from the relevant ministries regarding how to use the applications that have been launched.